ANALISIS KESALAHAN SISWA DALAM MEMECAHKAN MASALAH FUNGSI KOMPOSISI BERDASARKAN KRITERIA ENNIS - Ersa Oktavianti; Rahman Haryadi; Dwi Oktaviana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze students' errors in solving composition function problems based on the Ennis Criteria. This research uses a qualitative approach and the type of research is descriptive. The research subjects were class XI students of SMA Negeri 1 Belitang Hilir. The instrument in this research is test questions which are analyzed using the Ennis criteria indicators and interview guidelines. Based on the results of data analysis, it was concluded that students (1) with high abilities made mistakes in the situation and overview criteria; (2) Medium ability students make mistakes in the inference, situation and overview criteria; (3) Low ability students make mistakes in the criteria of focus, reason, inference, situation, clarity and overview.